Cancer: but what if it were a disease caused by an association between microorganisms? - Karla Lais Pêgas (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Despite the advances in knowledge of the neoplasm behavior, the exact understanding of the biological processes that involve the malignant tumors is not yet fully elucidated. Mechanisms such as subversion of phagocytosis, cytokines and chemokines expression, blocking of immunity and apoptosis regulation are recognized ways of tumor survival. Several of these mechanisms are also used as survival strategies of microorganisms. This article makes an analogy and compares the biological behavior of bacteria, viruses and neoplasms, showing several common points in their mechanisms of growth and survival, questioning cancer as a distinct living organism and introducing the hypothesis of synergy between viruses and bacteria in the development of neoplasms. Up to now, there are no experimental studies that effectively investigate the association between more than one microorganism as an etiologic factor of cancer.